Assessment of Development Results - Iraq - United Nations Development Programme (United Nations, 2015)
This Assessment of Development Results (ADR) in Iraq was conducted by the Independent Evaluation Office (IEO) of the United Nations Development Programme (UNDP) in 2013 towards the end of the current UNDP programme cycle of 2011–2014 with a view to contributing to the preparation of the new UNDP country programme as well as the forthcoming United National Development Assistance Framework (UNDAF). The ADR assesses the strategic positioning of UNDP support in transition and development. The ADR covers a particularly important time for Iraq, in its efforts towards reconstruction and transition to development.